Penyelidikan Epidemiologi Kejadian Luar Biasa (KLB) Difteri : Literatur Review - Pomarida Simbolon; Angela Br Surbakti; Angeli Br Surbakti (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Diphtheria is a type of infectious disease that can be prevented by immunization. The cause of diphtheria is toxigenic Corynebacterium diphtheriae strains. Humans are the only reservoir for the spread of diphtheria which is transmitted either through droplets, through eating utensils, as well as through close direct contact with skin lesions. This disease is characterized by sore throat, fever, malaise, and on examination pseudomembranes are found in the tonsils, pharynx and/or nasal cavity. Objective: To find out the magnitude of the Diphtheria outbreak problem and the risk factors that influence it. Method: This research is a literature study. The search was carried out in the Google Scholar database published in the period 2013 to 2023. Results: Shows that in extraordinary cases of diphtheria there are some who have received the DPT vaccine and there are also those who have not received the DPT vaccine, as well as a lack of public knowledge regarding diphtheria which can lead to outbreaks diphtheria. Conclusion: Epidemiological investigations of diphtheria outbreaks at this stage are still influenced by several factors which often occur, namely incomplete coverage of DPT vaccine in the toddler group, diphtheria transmission is prone to occur in the age group ≤ 15 years and low level of knowledge of the population due to lack of providing education about diphtheria disease.